Association of a child’s mental disorder with parental income and employment: analysis of nationwide register-based cohorts in Finland and Denmark - Natalie C Momen; Oleguer Plana-Ripoll; Christian Hakulinen; Marko Elovainio; Petri Böckerman; Kaisla Komulainen; Ripsa Niemi; Mai Gutvilig (BMJ Mental Health)
Background The onset of a severe physical illness of a child has been associated with earnings and employment losses among parents, but less is known in the context of children’s mental disorders.Objectives We estimated parental income and employment trajectories associated with a child’s mental disorder diagnosis in nationwide register-based cohorts from Finland and Denmark.Methods All parents whose child was diagnosed with a mental disorder (F00–F99 in ICD-10) at ages 1–25 in Finland and in Denmark during 1994–2019 were matched 1:1 to parents with a child without a mental disorder on psychiatric and sociodemographic characteristics. Generalised estimating equations were used to estimate the associations of a child’s mental disorder with parental annual income and employment outcomes from 5 years before to 5 years after the child’s diagnosis.Findings In 1994–2019, over one million parents in Finland and Denmark had at least one child diagnosed with a mental disorder at age 1–25. Parents exposed to a child’s mental disorder had consistently lower income and were more often unemployed compared with the matched unexposed parents, already 5 years before the child’s diagnosis. These differences became slightly larger over time, especially in analyses on strata involving parents whose child was diagnosed at a younger age. However, there was no consistent evidence of a change in parental annual income or employment around the time of their child’s diagnosis.Conclusions Our analysis shows that even in countries with strong welfare systems, a younger child’s mental disorder may contribute to widening socioeconomic inequity among families. However, the inequity in children’s mental health appears to primarily exist prior to, rather than in response to, a child’s mental disorder.Clinical implications Clinical and policy efforts should prioritise addressing pre-existing socioeconomic vulnerabilities for effective primary prevention of children’s mental disorders.